Perlindungan Terumbu Karang di Pulau Tikus Provinsi Bengkulu Berdasarkan Peraturan Daerah (PERDA) Provinsi Bengkulu Nomor 5 Tahun 2019 - Marisa Putri; Efti Restiana; Ema Septaria; M. Ilham Adepio (Jurnal Hukum dan Sosial Politik, 2025)
Indonesia, as an archipelagic nation with a vast marine territory, possesses significant coral reef ecosystems, including those in Bengkulu. However, the condition of coral reefs in Bengkulu has suffered damage due to human activities and natural factors. The Bengkulu Provincial Government issued Regional Regulation Number 5 of 2019 concerning the Management of Coastal Areas and Small Islands as a protective measure, but the effectiveness of its implementation has not been optimal. This research aims to analyze the implementation of this Regional Regulation in the protection of coral reefs in Bengkulu waters and to identify the challenges faced. Employing a normative legal research method with a literature study, this research examines laws and regulations, scientific literature, and related news. The research results indicate that the Regional Regulation has been implemented through various programs such as coral reef restoration, marine debris management, and socialization. However, its effectiveness is hampered by a lack of public awareness, weak supervision, and insufficient control over tourism activities. Further efforts are needed to increase public awareness, strengthen supervision, and manage tourism activities sustainably to achieve effective coral reef protection in Bengkulu.